Development of models of the technical condition of electrical equipment for calculating of reliability of power supply systems - Yu. A. Sekretarev; A. A. Gorshunov (Вестник Северо-Кавказского федерального университета)
Introduction. The article examines the inﬂuence of the current technical condition of electrical equipment on the reliability of power supply systems. Currently, there is little or no statistical information available that would help establish the dependence of failures in elements of power supply systems on the occurrence and development of defects in the details of these elements when monitoring their condition. In addition, there are also no mathematical models that could show the connection between these events in the equipment.Goal. The purpose of the work is to develop mathematical models for modeling and accounting for the current technical condition of elements of power supply systems in reliability calculations.Materials and methods. A mathematical model is proposed that allows taking into account the current technical condition of electrical equipment in reliability calculations. The mathematical model is based on a heuristic method of obtaining information, the weighting coeﬃcients of signiﬁcance obtained during the examination are used in the model. The examination was carried out by employees of the company of the object in question. A mathematical model has been developed to generate the values of the current technical condition of the elements and to model the weight coeﬃcients of the condition, to account for defects in the elements of the power supply system when calculating reliability.Results and discussion. The presented mathematical models were implemented in the form of a software package for automated calculation of the reliability of the power supply system and generation of values of the current technical condition based on the Monte Carlo method. To calculate the reliability of the considered power supply schemes, the main reliability indicators of the elements were used, obtained on the basis of statistical information on failures of electrical equipment over 10 years of operation.Conclusion. The calculation of circuit reliability for the consumers in question has been performed, and the current technical condition for their elements has been simulated. A comparison of reliability estimates with and without taking into account the current technical condition is given.